Cardiac rehabilitation and all-cause mortality in patients with heart failure: A retrospective cohort study. (11th May 2021) - Buckley, B; Harrison, S; Fazio-Eynullayeva, E; Underhill, P; Sankaranarayanan, R; Wright, D; Thijssen, D; Lip, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Despite the benefits of exercise training in the secondary prevention of cardiovascular disease, there are conflicting findings for the impact of exercise-based cardiac rehabilitation (CR) on mortality for patients with heart failure (HF). Methods: A retrospective cohort study was conducted which utilised a global federated health research network. Patients with a diagnosis of HF were compared between those with and without an electronic medical record of exercise-based CR within 6-months of a HF diagnosis. Patients with HF undergoing exercise-based CR were propensity score matched to HF patients without exercise-based CR by age, sex, race, co-morbidities, medications, and procedures. We ascertained 2-year incidence of all-cause mortality, hospitalisation, stroke, and atrial fibrillation. Results: Following propensity score matching, a total of 40, 364 patients with HF were identified. Exercise-based CR was associated with 42% lower odds of all-cause mortality (odds ratio 0.58, 95% confidence interval (CI): 0.54-0.62), 26% lower odds of hospitalisation (0.74, 95% CI 0.71-0.77), 37% lower odds of incident stroke (0.63, 95% CI 0.51-0.79), and 53% lower odds of incident atrial fibrillation (0.47, 95% CI 0.4-0.55) compared to matched controls. The beneficial association of exercise-based CR on all-cause mortality was consistent across stratification for sex, older age, included comorbidities, and HF subtype (all P < 0.0001), including patients with HFpEF (0.65, 95% CI 0.60-0.71). Conclusions: Exercise-based CR was associated with lower odds of all-cause mortality, hospitalisations, incident stroke and incident atrial fibrillation at 2-years follow-up for patients with HF. The beneficial association of CR and lower mortality was consistent for patients with HFrEF and HFpEF.